2020
DOI: 10.1186/s12905-020-01100-8
|View full text |Cite
|
Sign up to set email alerts
|

Women’s experiences of receiving a diagnosis of premenstrual dysphoric disorder: a qualitative investigation

Abstract: Background Premenstrual dysphoric disorder (PMDD) is a complex and disabling condition that affects women of reproductive age, characterised by severe physical and psychological symptoms that occur cyclically and remit following the onset of menses. As the psychological nature and consequences of PMDD often seem indistinguishable from symptoms of other mental health difficulties, this condition presents distinct diagnostic challenges for healthcare professionals. Therefore, this study aimed to explore women’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 35 publications
(45 reference statements)
4
31
0
Order By: Relevance
“…Many forms of treatment and self-care are available to control the symptoms of most women, but 3 in 4 women suffer from some form of PMDD ( 11 ). Another common menstrual disorder is Dysmenorrhea (primary and secondary), which refers to pain during menstruation.…”
Section: Introductionmentioning
confidence: 99%
“…Many forms of treatment and self-care are available to control the symptoms of most women, but 3 in 4 women suffer from some form of PMDD ( 11 ). Another common menstrual disorder is Dysmenorrhea (primary and secondary), which refers to pain during menstruation.…”
Section: Introductionmentioning
confidence: 99%
“…I know it's not my fault, which is probably the main thing, I know it's not my fault now, I'm not just a bad person. (Participant 3) (Reported in Osborn et al 2020a) Women diagnosed with PMDD reported feelings of recognition, and of being really heard. They also detailed how the diagnosis transformed their identities and self-understanding, a transformation some described as lifesaving.…”
Section: Assessing the Medicalization Of Pmdd In The Dsmmentioning
confidence: 99%
“…I couldn't, I didn't want to get out of bed in the morning, couldn't sleep at night, erm … just doing stupid things like ripping wallpaper off because I couldn't cope with the anxiety, the feeling of the anxiety. (Reported inOsborn et al 2020a) Of course, more research needs to be conducted before we are able to conclude (or overrule) that the medicalization of PMDD is unanimously or mostly welcomed by individuals living with associated symptoms.14 But these findings suggest that if individuals with PMDD were included in the discussions related to the introduction of PMDD in the DSM-5, they could have asked for its introduction. This would mean that patient requests are in part compatible with the decision of the panel in charge of PMDD.…”
mentioning
confidence: 99%
“… 1 These chronic and cyclic conditions have profound effects on quality of life 2 and major health consequences (eg, suicidal behavior 3 and hypertension 4 ). Although the peak age of receiving a clinical diagnosis is in the 30s, 5 recent work 6 revealed that 70% of individuals with PMDs had symptom onset in adolescence, suggesting that early life factors may contribute importantly to etiology. However, few childhood risk factors have been identified for PMDs, except for childhood abuse 7 and pubertal timing.…”
Section: Introductionmentioning
confidence: 99%